CHARACTER EDUCATION THROUGH INTEGRATION OF LOCAL AND GLOBAL VALUES - Luthfi, Attabik (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2024)
Character building is one of the main goals of education in the contemporary era full of global challenges. This article discusses the importance of integrating local and international values in building the character of the younger generation. Local values rooted in the nation's culture and traditions are important in shaping individual identity and morality. In contrast, global values such as tolerance, openness, and technological progress are important foundations in facing an increasingly connected world. Contemporary issues such as social change, technological disruption, and globalization require education to adapt to a more inclusive and dynamic approach. This study employs a qualitative methodology, utilizing a descriptive approach. Through a balanced integration of local and global values, education can build the character of Sith who have a moderate attitude, and broad insight, and can contribute positively to the life of the worldwide community without leaving the nation's identity. This study highlights educational strategies in dealing with contemporary issues and the important role of teachers and academic institutions in forming strong and adaptive characters. The integration of local and global values in education is key to building a strong and relevant character amidst the challenges of the times. With a balanced and flexible approach, students can grow into individuals who are firmly rooted in their local values, while being able to face and contribute to an ever-changing global world.